ASSOCIATION BETWEEN SLEEP DISORDERS AND CHRONIC DISEASES IN PATIENTS OF THE BRAZILIAN NATIONAL HEALTH SYSTEM - Luana Carolina de Morais; Everton Alex Carvalho Zanuto; Dayane Cristina Queiroz; Monique Yndawe Castanho Araújo; Ana Paula Rodrigues Rocha; Jamile Sanches Codogno (Journal of Physical Education)
ABSTRACT Many factors are associated with sleep disorders, causing an increase in health spending. The objective of this study was to analyze the association of sleep disorders and non-communicablechronic diseases in patients over 50 years of age, attended by Basic Health Care Units of Presidente Prudente. In total, 363 patients participated. The history of diseases was self-reported through the use of a questionnaire, the level of physical activity was evaluated by the Baecke questionnaire, and sleep quality was assessed using the Mini-Sleep Questionnaire. Anthropometric and body composition data were collected using a stadiometer and scale; patients in the highest (75th) percentile were considered obese. Statistical analysis was performed using the Student t test, chi-square test, and binary logistic regression. The results showed that sleep disorders are associated with osteoporosis, arthritis/osteoarthritis, low back pain, depression, and obesity. Additionally, obesity and physical inactivity influence the occurrence of non-communicable chronic diseases.